Clinical Handbook of Insomnia - Attarian, Hrayr P.; Attarian, Hrayr P.; Schuman, Catherine.; Schuman, Catherine. (Current Clinical Neurology,, 2010)
When first published in 2003, this indispensable handbook fulfilled a critical need for information about the various causes of insomnia. Updated and expanded, this new edition of the Clinical Handbook of Insomnia offers healthcare providers the latest diagnostic and treatment strategies, as well as research developments, in the field of insomnia. With contributions from an expanded team of leading researchers from 5 different countries, this important resource includes new chapters on insomnia in special populations such as children, in adolescents, in the geriatric population, in menopausal women, and during pregnancy. The first edition chapter on insomnia in other sleep disorders has been divided and expanded into three comprehensive chapters addressing insomnia in sleep-related breathing disorders, in circadian rhythm disorders, and in sleep-related movement disorders and other parasomnias. The chapter on insomnia in neurological and medical disorders has also been split into two; an expanded one on neurological illness and another on medical disorders. There is also a new chapter on the association between insomnia and pain disorders, and, crucially, a practical ‘how-to’ chapter aimed at mid-level clinicians. The Clinical Handbook of Insomnia 2nd edition also includes state-of-the-art discussion of important developments made in recent years. Along with an overview of significant advances in the treatment of insomnia, including four new medications granted FDA approval and a number of others in the pipeline, the text offers a wealth of of new data regarding the pathophysiology of insomnia. Complete with a host of case studies, charts, and graphs to illustrate the material, the Clinical Handbook of Insomnia 2nd edition continues to fill an important niche in the literature by addressing the issue in its multiple forms and by presenting the information to clinicians in an easily accessible format.